Relationship Between the Use of Boots and the Incidence of Tinea Pedis in Motor Vehicle Wash Employees in Jambi City - Hasibuan, Fitra Husni Mubarak; Hanina; Aurora, Wahyu Indah Dewi; Lipinwati; Maharani, Citra (Journal of Medical Studies, 2025)
Background: Tinea pedis is a fungal infection of the skin of feet characterized by peeling skin, itching and watery skin. Risk factors for this disease are working in wet places and wearing closed shoes for a long time such as motor vehicle wash service workers. The purpose of this study was to determine the relationship between the use of boots and the incidence of tinea pedis in motor vehicle wash employees in Jambi City. Objective: This study aims to determine the relationship between the use of boots with the incidence of tinea pedis in motorbike wash employees in Jambi City Methods: This quantitative analytical research type with a crosssectional method The research sample was motor vehicle wash employees in Jambi City. The sampling technique used the cluster sampling method, researchers selected groups in each sub-district in Jambi City according to the research criteria as many as 96 samples. Data were obtained using questionnaires, physical examinations and KOH examinations. The data that had been obtained were then processed by computerization using the SPSS application. Results: In this study, it was found that there was a significant relationship between length of work and the incidence of tinea pedis, length of use of boots with the incidence of tinea pedis and foot hygiene with the incidence of tinea pedis. Representatively p-value less than 0.005 (p=0.016) (p=0.000) (p=0.000). Conclusion: The longer working in a humid place, the longer using boots, and the worse foot hygiene a person has increases the risk of getting tinea pedis